Assessment of concrete-to-concrete shear bond behavior using 3-D direct shear testing - Mohamad Ezzedine El Dandachy; Dalia AlMohamad; Matthieu Briffaut; Abdulkader El-Mir; Joseph J. Assaad; Hilal El-Hassan (Results in Engineering)
The interfaces that develop when fresh concrete is poured onto existing substrates are noted for their vulnerability and influence on the durability and integrity of the composite structure. Studies on the shear bond properties and failure mechanisms of such composite concrete-to-concrete joints under normal stress are essential for developing predictive and numerical models that accommodate various levels of joint substrate roughness. This study aims to use an innovative 3D shearing box, BCR3D, to analyze the shear behavior of concrete-to-concrete joints under direct shear tests at a constant normal stress. The influence of the degree of surface roughness on the pure shear behavior of these joints was assessed at a normal stress level of 1 MPa. The substrate post-hardening surface morphology was evaluated using a high-resolution laser profilometer. Statistical surface roughness parameters were computed using MATLAB. A parametric study was carried out involving bond strength, residual shear stress, contractive-dilative behaviors, and total fracture energy. Results showed that bond strength, dilative normal displacement, and total fracture energy were proportional to the substrate surface roughness. Residual shear stress was not affected by the initial surface roughness. Dilative normal displacements were more significant for specimens with higher surface substrate roughness due to interlocking, with values reaching up to 1.77 mm. Joints with high substrate surface roughness exhibited similar bond strength and fracture energy to those obtained from the monolithic specimens, underscoring the significance of substrate preparation before casting new concrete layers.